PKMS PEMBERDAYAAN IBU RUMAH TANGGA BERBASIS EKONOMI KREATIF MELALUI USAHA PEMBUATAN KUE TRADISIONAL DI BANJAR BLAHTANAH SUKAWATI - Putu Dian Pradnyanitasari; Putu Yudha Asteria Putri; Ida Ayu Agung Idawati (Jurnal Abdi Masyarakat, 2019)
Market snacks are foods that are usually bought from traditional markets. Until now the market snacks are still very popular for family snacks and served to guests. One type of market snacks that are well known from any times to the present is the sagon cake. In Bali the sagon cake which is commonly called "jaje sagon" is very popular, especially when it is approaching the feast day of "jage sagon" which is very popular in the market. This traditional cake made from coconut and sticky rice flour is the result of production from a home industry (IRT) business using simple equipment. The problems faced by partners include: 1) Do not have a bookkeeping or records related to income, expenses, production costs and profit and loss. 2) Do not have knowledge about management accounting practices related to the calculation of cost of production, cost of orders, capital budgeting and the performance of UMKM in conducting their business activities. 3) Do not understand corporate governance. 4) Don't have a marketing system like social media. 5) Unattractive product packaging and lack of product variation. The solutions offered for this problem are 1) Assisting in making simple financial books and reports. 2) Assist and provide management accounting training. 3) Provide training on the application of corporate governance, especially relating to the determination of production and marketing strategies. 4) Make social media to help in product marketing and provide assistance in its use. 5) Help make new packaging more attractive so that it can increase marketing and make alternative jaje sagon that is more varied from more contemporary flavors or forms.